Establishment and characterization of a cell line from the head kidney of golden pompano Trachinotus ovatus and its application in toxicology and virus susceptibility. Issue 5 (8th March 2017) - Li, P.; Zhou, L.; Wei, S.; Yang, M.; Ni, S.; Yu, Y.; Cai, J.; Qin, Q.
Abstract : A cell line derived from the head kidney of golden pompano Trachinotus ovatus (TOHK) was established and characterized in this study. The TOHK cells grew most rapidly at 28° C and the optimum foetal bovine serum concentration in L‐15 medium was 10%. The TOHK cells have a diploid chromosome number of 2 N = 54. The transfection efficiency of TOHK cells was 7·5% at the 15th passage and 72% at the 40th passage. The transfection efficiency in TOHK cells was high, so these cells are suitable for foreign gene expression. The cytotoxic effects of heavy metals and extracellular products from Vibrio anguillarum and Vibrio alginolyticus were demonstrated in TOHK cells, so this TOHK cell line could also be applied in environmental monitoring of heavy metals and pathogenic bacteria. TOHK cell line showed high virus susceptibility, such as grouper nervous necrosis virus (GNNV) and Singapore grouper iridovirus (SGIV). Then, TOHK cell line could be used for the study of viral pathogenesis and the development of antiviral strategies.